PP.90 Risk Factors Associated with Intrauterine Deaths – Our Experience At District General Hospital. (26th April 2013) - Ling, HZ; Mulki, O; Hamid, R
Abstract : Objective: To identify the relationship between intrauterine death (IUD) and various demographics, medical and obstetrics risk factors relating to the local population in Ealing. Methods: There were 47 booked, singleton IUD cases amongst 7464 births in Ealing Hospital between April 2010 to September 2012. We retrospectively analysed the medical and obstetrics risk factors of IUDs (fetus ≥24/40 with absent fetal heart activity in-utero) in the local population. Results: IUD occurred in 0.63% of all birth. Females of Asian origin are at increased risk of IUD (45%) compared to other ethnicities. Lifestyle risks like smoking and alcohol posed no significant increase in risk to the Ealing population, and consanguineous relationships only accounted for 8.5% of the cases. IUD was most prevalent amongst the young (20–25) primips (59.5%) with BMI > 25 (68%), mostly occurring between 37–40 weeks (47.7%). Majority of them were booked ≤12/40 (63.8%), had Dating and Anomaly scans, (87.2%, 89.3% respectively), low risk on antenatal screening (59.5%). Interestingly, previous caesarean section (6.3%) was the most prevalent in obstetrics history. 68% had presented antenatally with reduced fetal movements, vaginal bleeding or abdominal pain. Maternal conditions like Diabetes (4.2%), Obstetrics Cholestasis (2.1%) and Preeclampsia (10%) were not strongly associated with the IUD cases, indicating robust antenatal surveillance we provide to high risk women. Conclusion: While further studies aiming to modify IUD risk factors are needed, careful planning on timing of induction of labour should be carried out specifically in young, Asian primips with BMI > 25 who present antenatally with significant episode(s).